Upaya Perlindungan Hukum Terhadap Anak Luar Nikah: Analisis Yuridis dalam Perspektif Hukum di Indonesia - Shafira Rizka Azzahrani (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research focuses on children born out of wedlock, based on all aspects that will arise for these children. And the provisions that will apply to the child born out of wedlock, such as their lineage, inheritance, and rights as a child, both from the perspective of religious law and positive law. The purpose of this research is to find out what efforts can be made to protect children from the consequences of adultery. This research is a normative legal study, with data sources obtained thru literature review based on the Quran and Hadith, books, legislation, and other related matters. A child born out of wedlock has no kinship ties with their biological father, but that does not mean the father who impregnated the mother can escape responsibility toward the child. The man who caused her pregnancy is obligated to meet all her needs and provide an inheritance thru a mandatory will so that the child receives fair treatment and thus achieves welfare in life. In this case, to realize child protection, there are efforts that can be made, namely: structure, substance, and legal culture. The court institution, as a legal structure, plays a very important role in applying and enforcing the law to ensure legal protection for the fulfillment of the rights of children born out of wedlock.